Apparatus Resources Development Model in Capacity Building Perspective (Study at Bone Bolango Regency Government of Gorontalo Province) - Udin Hamim; Djafar Ibrahim (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is using qualitative approach with a view to examine various phenomena related to human resources in public sector development model in capacity building perspective and alternative solution. Data collection is done through interview, observation and documentation.Based on research results, it can be inferred that the design of human resources in the public sector development still follow model arranged by Central or Provincial Government , the program is routinized, and coordination and cooperation not exist in the designing program. The implementation of human resources in public sector development conducted through: first, recruitment, mutation is a means for apparatus recruitment process and this process hasn’t based on rationality of requirement conformity and competence. Second, education and training are not based on real needs of the region, not opened in nature, and not used effective and efficient principles. Third, promotion on structural position is conducted without tacking account job analysis and still influenced by political rationality, ethnicity. Baperjakat has weak authority. As expansion area, the implementation of human resources in public sectors development in Bone Bolango Regency faced with obstacle form internal and external factors. Internally, there exist some factors such as: limited apparatus resources capacity, limited authority, promotion and mutation did not based on job analysis and determined by Leader (Bupati). The external factors among other are politic, ethnicity, and economic condition and lack of cooperation with relevant parties, those factors will hamper the implementation of human resources in public sector development in expansion area government environment.Keywords: capacity building, human resources in public sector, Local Government